Atrial Lesions in a Pedigree With PRKAG2 Cardiomyopathy: Involvement of Disrupted AMP-Activated Protein Kinase Signaling - Chen, Shaojie; Lin, Yongping; Zhu, Yue; Geng, Le; Cui, Chang; Li, Zhaomin; Liu, Hailei; Chen, Hongwu; Ju, Weizhu; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
PRKAG2 cardiomyopathy is a rare progressive disease characterized by increased ventricular wall thickness and preexcitation. Dysfunction of the protein 5′-AMP-activated protein kinase (AMPK) plays a decisive role in the progression of ventricular lesions. Although patients with the PRKAG2-R302Q mutation have a high incidence of atrial fibrillation (AF), the molecular mechanism contributing to the disease remains unclear. We carried out whole-genome sequencing with linkage analysis in three affected members of a family. Atrial samples were obtained from the proband via surgical intervention. Control atrium biopsies were obtained from patients with persistent AF. Pathological changes were analyzed using the hematoxylin and eosin (H&E), Masson, and periodic acid–Schiff (PAS) staining. The AMPK signaling pathway was investigated by western blot. A murine atrial cardiomyocyte cell line (HL-1) and human induced pluripotent stem derived atrial cardiomyocytes (hiPSC-ACMs) were transfected with an adenovirus carrying the same mutation. We used enzyme linked immunosorbent assay (ELISA) to determine the AMPK activity in HL-1 cells and hiPSC-ACMs overexpressing PRKAG2-R302Q. Pathological results showed a large quantity of glycogen accumulation and vacuolization in cardiomyocytes from the proband atrial tissue. Western blot analysis revealed that the AMPK activity was significantly downregulated compared with that of the controls. Furthermore, remarkable glycogen deposition and impairment of AMPK activity were reproduced in HL-1 cells overexpressing PRKAG2-R302Q. Taken together, PRKAG2-R302Q mutation directly impair atrial cardiomyocytes. PRKAG2-R302Q mutation lead to glycogen deposition and promote the growth of atrial lesions by disrupting the AMPK pathway.